2022
DOI: 10.3389/fmed.2021.780005
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Use of Low Tidal Volume Ventilation in COVID-19—Insights From the PRoVENT–COVID Study

Abstract: The purpose of this study was to compare and understand differences in the use of low tidal volume ventilation (LTVV) between females and males with acute respiratory distress syndrome (ARDS) related to coronavirus disease 2019 (COVID-19). This is a post-hoc analysis of an observational study in invasively ventilated patients with ARDS related to COVID-19 in 22 ICUs in the Netherlands. The primary endpoint was the use of LTVV, defined as having received a median tidal volume (VT) ≤6 ml/kg predicted body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is well known that women are better at producing autoantibodies than men and are at higher risk for most autoimmune diseases. However, there is a sex difference in COVID‐19 severity that men tend to be more severe compared to women, 27,28 which may not be explained by autoantibody‐mediated COVID‐19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that women are better at producing autoantibodies than men and are at higher risk for most autoimmune diseases. However, there is a sex difference in COVID‐19 severity that men tend to be more severe compared to women, 27,28 which may not be explained by autoantibody‐mediated COVID‐19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…47 We believe these findings are also evidence that improving the utilization of LTVV within a hospital system is an achievable area of process improvement both inside and outside of ICUs. In prior literature, female sex and elevated BMI have frequently been reported as factors associated with inappropriately high tidal volumes, 12,18,4953 our stratified analysis found that these subgroups were still more likely to receive LTVV inside the ICU than outside (Supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 62%